Integrated assessment of introduced red currant cultivars under the conditions of Tambov Province - O. S. Rodyukova (Труды по прикладной ботанике, генетике и селекции)
Background. Today, the effectiveness of berry crop cultivation depends on correct formation of the regional assortment of cultivars, taking into account the instability of environmental factors. Searching for and accumulating genetic resources from leading breeding centers, both domestic and foreign, as well as studying new genotypes under local conditions would make it possible to identify berry crop varieties for production and breeding.Materials and methods. This study was conducted in Michurinsk, Tambov Province, on the experimental plantations of red currant at the I.V. Michurin Federal Science Center in 2016–2020. The research material consisted of 15 introduced cultivars of red currant. Collection testing was carried out in line with generally accepted techniques of variety studies and field experiments.Results. Under the conditions of Tambov Province, the introduced red currant cultivars required a sum of temperatures of 89.3–132.0°C to start growing, 290.0–328.0°C to start flowering, 943.5–1133.0°C to start ripening, and 1478.2–1733.3°C to produce fully matured berries. Cvs. ‘Belosnezhka’, ‘Lvovyanka’, ‘Oksamit’ and ‘Rosinka’ showed complex resistance to diseases and pests. Cvs. ‘Kalinka’, ‘Lasunya’, ‘Lider’, ‘Lvovyanka’, ‘Oksamit’, ‘Orlovskaya zvezda’ and ‘Sara’ produced large fruits. Stable high productivity and yield were observed in cvs. ‘Vika’, ‘Lider’, ‘Oksamit’, ‘Orlovskaya zvezda’ and ‘Rosinka’. A close correlation (r = 0.99) was recorded between the productivity per bush (kg) and yield (100 kg/ha), and medium correlations between the berry weight and productivity per bush (r = 0.69), and between the productivity per one linear meter of branches and productivity per bush (r = 0.35).Conclusion. As a result of the integrated assessment under the conditions of Tambov Province, the red currant cultivars ‘Vika’, ‘Lider’, ‘Oksamit’, ‘Orlovskaya zvezda’ and ‘Rosinka’ were recommended for cultivation.